Pendampingan Peningkatan Literasi dan Semangat Membaca Santri Pesantren Hidayatul Islam melalui Kegiatan Pembacaan Buku dan Presentasi Lisan - Pranoto Effendi (Jurnal Masyarakat Mengabdi Nusantara, 2025)
Literacy, specifically reading, is a crucial skill for Islamic students (santri). Reading opens the door to knowledge. This article reports on literacy-boosting activities for students at the Al-Hidayah Quranic Islamic Boarding School to encourage their enthusiasm for reading. These activities include giving students reading assignments. They choose books they enjoy and have access to. Within a week, they complete their homework by reading and studying the book. At the next meeting, they are tasked with presenting what they have read and the benefits they can gain from the book's contents. The presentation is delivered orally without the aid of PowerPoint. Skills honed in this mentoring include the courage to speak freely, summarize the book's contents, extract wisdom, and the ability to persuade listeners. This activity is expected to not only improve the students' literacy skills but also shape their character, enabling them to convey information effectively and confidently. Thus, this activity plays a role in developing communication skills that will be useful for their future lives, both within the Islamic boarding school environment and in the wider community.Islamic boarding school students